2012
DOI: 10.1039/c2jm35267b
|View full text |Cite
|
Sign up to set email alerts
|

A novel carbazole-based dye outperformed the benchmark dye N719 for high efficiency dye-sensitized solar cells (DSSCs)

Abstract: Two novel high molar extinction coefficient heteroleptic Ru(II) isomers, NCSU-10 and NCSU-10 0 , based on carbazole antenna were synthesized with the aid of Knoevenagel reaction, to study the influence of the carbazole antenna and anchoring group (COOH) isomerization on the light harvesting efficiency (LHE), ground and excited state oxidation potentials, incident-photon-to-current conversion efficiency (IPCE), short-circuit photocurrent density (J SC ), and total solar-to-electric conversion efficiency (h) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 39 publications
3
53
0
Order By: Relevance
“…This effect can be attributed to the extended π-conjugation and stronger electron donating carbazole ligand, which resulted in destabilization of the metal-based HOMO (t 2g ), and that translated into red shifted absorption spectra due to the decreased HOMO-LUMO gap for HD-14-15 compared to that of N719, as shown schematically in the energy level diagram of Figure 4. Additionally, incorporation of stronger ancillary ligands for HD-14 and HD-15 resulted in stronger emission than N719 as being previously reported for NCSU-10 and MH11 19,25 . Hence, it is expected that under similar conditions and concentration, HD-14 and HD-15 are less prone to radiation-less energy losses through internal conversion and/or intersystem crossing compared to N719.…”
Section: Photophysical Measurementssupporting
confidence: 59%
See 1 more Smart Citation
“…This effect can be attributed to the extended π-conjugation and stronger electron donating carbazole ligand, which resulted in destabilization of the metal-based HOMO (t 2g ), and that translated into red shifted absorption spectra due to the decreased HOMO-LUMO gap for HD-14-15 compared to that of N719, as shown schematically in the energy level diagram of Figure 4. Additionally, incorporation of stronger ancillary ligands for HD-14 and HD-15 resulted in stronger emission than N719 as being previously reported for NCSU-10 and MH11 19,25 . Hence, it is expected that under similar conditions and concentration, HD-14 and HD-15 are less prone to radiation-less energy losses through internal conversion and/or intersystem crossing compared to N719.…”
Section: Photophysical Measurementssupporting
confidence: 59%
“…Recently, our group reported a much simple yet highly efficient sensitizer NCSU-10 19 based on carbazole bipyridyl ancillary ligand. The corresponding bipyridyl ancillary ligand was synthesized by one step Knoevenagel type condensation reaction [19][20][21][22] . Sensitizer employing that ancillary ligand was coded as NCSU-10 and is shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of charge localization in dcbpy, there exists an appreciable electron injection from the excited dye to the conduction band of TiO 2 . It is well known that N719 shows weak photoluminescence in the 650 and 800 nm [11], whereas sensitizers S1 and S2 do not…”
Section: Uv-visible Absorption Propertiesmentioning
confidence: 98%
“…In this context, highly extended conjugation units such as thiophene [2], ethylenedioxythiophene (EDOT) [3], triphenylamine [4,5] and alkoxybenzene [6][7][8] attached to the bipyridyl ligand were designed to prepare novel sensitizers that exhibit an enhanced molar absorptivity in combination with a red-shifted absorption band. Few research groups revealed that ruthenium sensitizers containing carbazole hole transporting units in the bipyridyl ligand enhance the spectral response and energy conversion efficiency of DSSC's [9][10][11][12][13]. Particularly, Shafei et al [11] reported a novel carbazole containing ruthenium sensitizer exhibiting low energy MLCT peak at 545 nm with high molar absorptivity (2.06 x 10 4 M -1 cm -1 ) and extended absorption into the near IR region (ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation